A case of non-HPV related primary endometrioid adenocarcinoma of the cervix - Kieran Seay; Bethany Bustamante; Seema Khutti; Marina Frimer (Elsevier, 2020)
Objective: Primary endometrioid adenocarcinoma of the cervix is a rare subtype of adenocarcinoma that has often been misclassified in the literature due to the lack of clear-cut diagnostic criteria. A new classification system has recently been developed that aims to provide clarity and reproducibility when diagnosing subtypes of endocervical adenocarcinoma. This case report demonstrates the difficulty in diagnosing primary endometroid adenocarcinoma, application of the new diagnostic guidelines, and a review of the literature of this rare non-HPV subtype. Case: A 76 year-old women presented with postmenopausal bleeding and was found to have an exophytic cervical mass. Biopsies showed an adenocarcinoma of probable endometrial origin. She underwent a robotic-assisted simple hysterectomy with bilateral pelvic lymph node sampling and omental biopsy. Final pathology report demonstrated a primary endometrioid adenocarcinoma of the cervix, measuring 2.4 cm in size, diagnosed using the recently developed International Endocervical Adenocarcinoma Criteria and Classification (IECC) system. Patient was then treated with external beam radiation therapy and concurrent chemotherapy, followed by vaginal brachytherapy. She had no evidence of disease at her 15-month follow-up visit. Conclusion: Primary endometrioid adenocarcinoma of the cervix is a rare and diagnostically challenging tumor of the cervix. This case illustrates the challenges associated with diagnosis of this endocervical carcinoma subtype and the need for a multi-disciplinary approach when determining treatment.